2022
DOI: 10.1002/smll.202205647
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐II Fluorescence Imaging‐Guided Oxygen Self‐Sufficient Nano‐Platform for Precise Enhanced Photodynamic Therapy

Abstract: Tumor hypoxia and systemic toxicity seriously affect the efficacy of photodynamic therapy (PDT) and are considered as the “Achilles’ heel” of PDT. Herein, to combat such limitations, an intelligent orthogonal emissions LDNP@SiO2‐CaO2 and folic acid‐polyethylene glycol‐Ce6 nanodrug is rationally designed and fabricated not only for relieving the hypoxic tumor microenvironment (TME) to enhance PDT efficacy, but also for determining the optimal triggering time through second near‐infrared (NIR‐II) fluorescence im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Li et al fabricated NaYF 4 : Nd@NaGdF 4 @NaYbF 4 :Er@NaYF 4 LDNPs with independent orthogonal emission. [90] The downconversion luminescence of Nd 3+ in LDNPs was used for NIR-II fluorescence imaging to monitor nanomedicine drug delivery and tumor enrichment in vivo and to determine the optimal trigger time. Meanwhile, the upconversion luminescence of Er 3+ in LDNPs worked as an excitation light for chlorine e6 in PDT.…”
Section: Ldnps Based Nir-ii Imagingguided Therapymentioning
confidence: 99%
“…Li et al fabricated NaYF 4 : Nd@NaGdF 4 @NaYbF 4 :Er@NaYF 4 LDNPs with independent orthogonal emission. [90] The downconversion luminescence of Nd 3+ in LDNPs was used for NIR-II fluorescence imaging to monitor nanomedicine drug delivery and tumor enrichment in vivo and to determine the optimal trigger time. Meanwhile, the upconversion luminescence of Er 3+ in LDNPs worked as an excitation light for chlorine e6 in PDT.…”
Section: Ldnps Based Nir-ii Imagingguided Therapymentioning
confidence: 99%
“…These ROS can effectively induce apoptosis of cancer cells. Previous studies have shown that PDT therapy mediated by NIR-II FL can precisely locate the tumor, thus improving the efficiency of PDT and its anti-tumor effect [ 69 , 70 ]. Fan et al, designed and manufactured a capsaicin-modified semiconductor polymer nanoparticle (CSPN) to regulate the calcium ion channels of cancer cells ( Figure 10 a,b) [ 61 ], enabling calcium overload cancer treatment without the addition of additional calcium ( Figure 10 c).…”
Section: Nir-ii Pdots As Tumor Theranostic Platformsmentioning
confidence: 99%
“…These ROS can effectively induce apoptosis of cancer cells. Previous studies h shown that PDT therapy mediated by NIR-II FL can precisely locate the tumor, thus proving the efficiency of PDT and its anti-tumor effect [69,70]. Fan et al, designed Photodynamic therapy (PDT) is a new low-invasive, high-efficiency, and non-drugresistant tumor therapy [68].…”
Section: Nir-ii Pdots As Tumor Theranostic Platformsmentioning
confidence: 99%
“…However, the uncontrollability of oxygen release after immersion in water is an issue, especially for the oxygen-releasing hydrogels. CaO 2 nanoparticles have also recently been used in cancer therapies such as reactive oxygen-species-based chemodynamic therapy, , calcium overload cancer therapy, and photodynamic therapy. Although many researchers have used CaO 2 in cell culture conditions, the nanoscale surface chemistry of CaO 2 in these conditions has not been taken into account.…”
Section: Introductionmentioning
confidence: 99%